Effect of plyometric training on jumping, sprinting and change of direction speed in child female athletes - Bogdanis, G. C.; Donti, O.; Papia, A.; Donti, A.; Apostolidis, N.; Sands, W. A. (Sports, 2019)
This study examined the effects of 8 weeks of plyometric training on jumping, sprinting, and change of direction (COD) performance. Methods: Fifty female 7-9-year-old gymnasts were randomly assigned to a plyometric training group (PG; n = 33), that performed supplementary plyometric training twice per week, and a control group (CG; n = 17) that continued regular training. The following tests were performed before and after the intervention: 10 and 20 m sprints, 5 + 5 m and 10 + 10 m COD tests, one-leg and two-leg countermovement jump (CMJ), drop jump (DJ), squat jump (SJ), and standing long jump (SLJ). Results: Only a main effect for time was found for all jumping performance parameters (p = 0.001). However, the improvement of one- and two-leg CMJ in PG had a greater effect size than CG (0.72 and 0.67 vs. 0.34 and 0.18, respectively). Group × time interactions were found for 10 and 20 m sprint tests (p = 0.018 and p = 0.011, respectively) and for 10 + 10 m COD (p = 0.008) with the post hoc test showing improvement only for the PG (p = 0.001, 0.001, and 0.003 and d = 1.1, 1.14, and 0.6, respectively). Conclusions: Supplementary plyometric training increased sprint and COD performance more than regular gymnastics training, while jumping performance was equally improved in both groups